Spatial dynamics of a Sirex noctilio woodwasp population within a pine plantation in Patagonia, Argentina - Corley, Juan Carlos (2007)
The woodwasp Sirex noctilio F. (Hymenoptera: Siricidae) is probably the most important pest of pine tree plantations of the southern hemisphere. We studied the spatial arrangement of an endemic population of the woodwasp S. noctilio within pine plantations located in northwest Patagonia, Argentina, during three successive years since colonization. By censusing healthy and attacked trees, which provided data on current and past yearly woodwasp attacks, we studied: (i) the spatial pattern of attacked trees during the endemic phase of a woodwasp population, and (ii) the changes in the spatial arrangement through time and with an increasing (i.e., no intervention) pest population. Among a total of 53 649 counted trees, attack rates were low during the study period (accumulated attack below 0.5%). Results of spatial statistical analysis showed that woodwasp attack is highly clumped, and that spatial aggregation increases with time, even with increasing numbers of attacked trees. The observed spatial arrangement, a consequence of a demographic process, can have important implications for the management of woodwasp populations and contributes to our understanding of the nature of outbreak population behaviour in this pestiferous forest insect.